Exploring the relationship of supplier manufacturer with sourcing project success in-terms of strategic performance - Hassan, Mohamad Ghozali; Abdul Talib, Asmat Nizam; Abdullah, Rohani; Johari, Nor Azmi; Ismail, Mohd Azril (Atlantis Press, 2013)
The purpose of the current study was to investigate the relationship between relational-oriented exchange and outsourcing success of supplier-manufacturer relationship within Malaysia.This study used the partial least squares (PLS) and structural equation modeling (SEM) tool to test the hypotheses. The data was gathered from a postal survey of 865 electrical & electronics sub-sector, of which 216 respondents participated in this study.The result indicated that relational oriented exchange was positively related to the outsourcing success.Implications of the findings are further elaborated.